2004
DOI: 10.4049/jimmunol.172.6.3437
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Impaired Type 1 T Cell Responses to Influenza: Reduced Activation Ex Vivo, Decreased Expansion in CTL Culture In Vitro, and Blunted Response to Influenza Vaccination In Vivo in the Elderly

Abstract: The objective of this study was to analyze the changes in the type 1 T cell response, including the CD4+ Th1 and CD8+ T cell responses, to influenza in the elderly compared with those in young adults. PBMC activated ex vivo with influenza virus exhibited an age-related decline in type 1 T cell response, shown by the decline in the frequency of IFN-γ-secreting memory T cells specific for influenza (IFN-γ+ ISMT) using ELISPOT or intracellular cytokine staining. The reduced frequency of IFN-γ+ ISMT was accompanie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
137
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(149 citation statements)
references
References 37 publications
10
137
2
Order By: Relevance
“…Recently, it was shown that the numbers of spot-forming cells correlate with clinical protection from culture-confirmed influenza in young children (21). These numbers may vary depending on the antigen type and influenza strain, because median numbers in our assays were higher than those in assays in which hemagglutinin or vaccine components were used (9,(21)(22)(23), and as in the present study, A/H3N2-specific cell-mediated responses were lower than A/H1N1-specific responses. WIV contains core antigens in addition to surface antigens.…”
Section: Discussionsupporting
confidence: 58%
“…Recently, it was shown that the numbers of spot-forming cells correlate with clinical protection from culture-confirmed influenza in young children (21). These numbers may vary depending on the antigen type and influenza strain, because median numbers in our assays were higher than those in assays in which hemagglutinin or vaccine components were used (9,(21)(22)(23), and as in the present study, A/H3N2-specific cell-mediated responses were lower than A/H1N1-specific responses. WIV contains core antigens in addition to surface antigens.…”
Section: Discussionsupporting
confidence: 58%
“…The time range of the blood samples taken may account for these results with the second sample ( 13-39 days) which falls within the likely peak of the CD8 T cell response having a more significant effect on the results than the last timepoint sampled. Studies have shown that age impacts T cell responses to influenza vaccination, with elderly individuals (>65 yrs old) showing a decline in type 1 T cell responses which may be a factor in these results; however, the average age of our subjects was 44 years old with no individuals over the age of 60 [39,40]. The role of innate immunity components such as cytokines, dendritic cells, and toll like receptors in initiating influenza specific responses may also contribute to the discordance between these two arms of the immune system.…”
Section: Discussioncontrasting
confidence: 41%
“…We found that the following [10][11][12] and seasonal influenza vaccine. [13][14][15] Compromised nutritional status [16][17][18] and decreased T-cell activity [18][19][20] could be contributing factors for that finding. One study in patients with hepatitis C reported a decreasing effect of lower BMI on immune response to A(H1N1)pdm09 vaccine.…”
Section: Discussionmentioning
confidence: 99%